Phytocontact dermatitis mimicking a burn injury due to Ranunculus constantinopolitanus - Kose, R.; Okur, M. I.; Bingol, I.; Cetin, H. (Wiley, 2008)
[Abstract Not Available]
Keywords: burn; phytocontact dermatitis; Ranunculus constantinopolitanus